Corporate Social Responsibility in Media Digital During COVID-19 Pandemic - Raden Mas Try Ananto Djoko Wicaksono (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
The research aims to analyze corporate social responsibility (CSR) on social media in PT Tip Top during the COVID-19 Pandemic. Social media usage in corporate social responsibility activities allows the creation of an interactive horizontal dialogue between the company and stakeholders. The research would find out how PT Tip Top Supermarket implements Corporate Social Responsibility on Social Media. The research uses qualitative research methods with a case study approach. The author uses ‘holistic single case’ design. This research uses three sources of evidence, including direct observation, document analysis, and literature review. This research indicates that the CSR program on online media at PT Tip Top leads to the concept of corporate social marketing.